DYNAMIC OF FISHERMEN EXCHANGE RATE ON TUNA FISHERIES IN BITUNG CITY - Rizki Aprilian Wijaya (Pusbindiklat - LIPI, 2015)
Fishermen exchange rate (NTN) is one of the tools or indicator to see the welfare of fishing communities. This paper aims to analyze the structure of received value index, paid value index and dynamic of NTN. This study uses a quantitative approach through surveys. The study was conducted in the Batu Lubang Village, South LembehDistrict, Bitung City, North Sulawesi Province in 2012. 31 respondents determinent by purposive sampling. This research using value index as a NTN instrument, is the ratio between fishermen received value index (It) with the fishermen paid value index (Ib). The results showed that received value index is strongly influenced by theproduction and price of tuna catch. Paid value index is strongly influenced by the variable cost of fishing. Fishermen exchange rate index experienced a downward trend so that it can be said that the welfare of fishermen also decreased.